-8(t-7)-(t+8)=8

Simple and best practice solution for -8(t-7)-(t+8)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(t-7)-(t+8)=8 equation:


Simplifying
-8(t + -7) + -1(t + 8) = 8

Reorder the terms:
-8(-7 + t) + -1(t + 8) = 8
(-7 * -8 + t * -8) + -1(t + 8) = 8
(56 + -8t) + -1(t + 8) = 8

Reorder the terms:
56 + -8t + -1(8 + t) = 8
56 + -8t + (8 * -1 + t * -1) = 8
56 + -8t + (-8 + -1t) = 8

Reorder the terms:
56 + -8 + -8t + -1t = 8

Combine like terms: 56 + -8 = 48
48 + -8t + -1t = 8

Combine like terms: -8t + -1t = -9t
48 + -9t = 8

Solving
48 + -9t = 8

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-48' to each side of the equation.
48 + -48 + -9t = 8 + -48

Combine like terms: 48 + -48 = 0
0 + -9t = 8 + -48
-9t = 8 + -48

Combine like terms: 8 + -48 = -40
-9t = -40

Divide each side by '-9'.
t = 4.444444444

Simplifying
t = 4.444444444

See similar equations:

| 3x-10=40 | | 3(17-x)+12x=2(8-3x)+50 | | a-4=-25 | | 2(7-2x)= | | 15-3(5x-7)= | | 2x+3[x-2(4-2x)]= | | 1x+3x+5=6x-13 | | 10=2(1+0.10t) | | 3*(3x+2)=2*(x+9)-19 | | 2(c-8)=6c+4 | | 2*(3x-4)=2x+12 | | r^2+r-288=0 | | r^2+r-110=0 | | 3x-1y=12 | | 5=1/4(7x-12) | | 11=2/3(x-3) | | 4x^2+37x+9=0 | | 4t(t-1)=288 | | 3=2/3(10x+6) | | 5=1/7(4x+28) | | 4x+5a= | | 7=1/2(5x-8) | | 18x+11=12x+47 | | -8x+9=x+72 | | 18x+12=10x-4 | | -9x-3=-10x+2 | | 8x-7=9x-13 | | X^3=8x^2-9x+72 | | t^2=98 | | -4x-2x=-1-8 | | 22x+1=15x-34 | | r^2+2r-110=0 |

Equations solver categories